Musik Tradisional Jawa Janengan Yang Terlupakan (A Forgotten Javanese Traditional Music Janengan) - mukarom mukarom; Rochsun Rochsun (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2018)
Villagers of Waringinsari, Sukoharjo sub-district, Pringsewu district, Lampung province grows and develops from voluntary migrants from Java. They are a group of marginalized people economically, politically, socially and culturally, so they expected so much when migrating to get a better life for his family. Residents who occupy Waringinsari village as the voluntary migrants are from different regions. They were farmers who had come from the felds of Java (Central, East and West) to gain ground as a new livelihood. The question is why with all kinds of differences in the Javanese sub-culture they could then dissolve together, and then they feel just as Javanese (in the sense of not distinguishing which Javanese origin). The research was carried out to get an answer whether janengan contributing music as media of entertainment, communication and propagation for villagers of voluntary migrants in the Waringinsari village, Suhoharjo Sub-district, Pringsewu district, Lampung province. This research is qualitative. The data obtained show that janengan music does really as alternative music that is able to show the identity of the people of Java. Janengan identifes the Javanese sub-culture from Kebumen which later became the common property of the voluntary migrants. They feel a sense of musical art is proven fact that until now is still a viable alternative entertainment. Janengan also contribute to the cohesiveness, and was able to eliminate the bulkhead sub-culture of their respective regions of origin. Music janengan is able to be an alternative as a cheap entertainment media, as a means of gathering spontaneous migrants thus establish communication in the period since the beginning of the village to the present, the past 60 years. In addition, the content ofthe janengan music lyric also provide a moral message that as human beings they are not arrogant, and ableto follow prophets. Janengan is able to instill the values to the younger generation so that they can becomegood human in morality as told in the poem of janengan.